Marital Adjustment and Interleukin-6 (IL-6) - Whisman, Mark A. (2012)
Building on prior research that marital functioning is associated with a variety of health outcomes, we evaluated the association between marital adjustment and a marker of inflammation in a sample of married adults between the ages of 35 and 84 years old (N = 415) from the second wave of the population-based Survey of Midlife Development in the United States (MIDUS II). Specifically, we evaluated associations between positive (i.e., partner support) and negative (i.e., partner strain) dimensions of marital adjustment and interleukin-6 (IL-6) separately for men and women, and whether these associations were moderated by age. Results indicated that (a) marital adjustment was not associated with IL-6 in men, (b) age moderated the association between marital adjustment and IL-6 in women, (c) partner support and partner strain were associated with IL-6 in younger women, and (d) partner support but not partner strain was uniquely associated with IL-6 in younger women. The associations between marital adjustment and IL-6 in younger women were significant when controlling for demographic variables, health status indicators, health behaviors, depressive symptoms, and perceived stress. These findings suggest that IL-6 may be a useful biomarker for studying health-relevant biological responses within intimate relationships, and that young women, in particular, may exhibit increased inflammation when partner support is low.